Identification of animal spirits in a bounded rationality model: An application to the euro area - Tae-Seok Jang; Stephen Sacht (Kiel Institute for the World Economy (IfW), 2012)
In this paper we empirically examine a heterogenous bounded rationality version of a hybrid New-Keynesian model. The model is estimated via the simulated method of moments using Euro Area data from 1975Q1 to 2009Q4. It is generally assumed that agents' beliefs display waves of optimism and pessimism - so called animal spirits - on future movements of the output and inflation gap. Our main empirical findings show that a bounded rationality model with cognitive limitation provides a reasonable fit to auto- and cross-covariances of the data. This result is mainly driven by a high degree of intrinsic persistence in the output and inflation gap due to the impact of animal spirits on economic dynamics. Further, over the whole time interval the agents had expected moderate deviations of the future output gap from its steady state value with low uncertainty. Finally, we find strong evidence for an autoregressive expectation formation process regarding the inflation gap.
Keywords: C53; D83; E12; E32; 330; Animal Spirits; Bounded Rationality; Discrete Choice Theory; Euro Area; New-Keynesian Model; Simulated Method of Moments